The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1075/pc.17016.les
|View full text |Cite
|
Sign up to set email alerts
|

From conceptualization to constructions in Finnish as an L2

Abstract: This study traces the individual learning trajectories of an adult beginner L2 Finnish learner in expressing the extralinguistic concept of evaluation from a dynamic usage-based perspective. Our results provide support for the view of learner language as a dynamic system in which patterns wax and wane and in which a change in one component has the potential to affect the whole system. In the early stages of learning there was a strong preference to use lexical verbs first, and then adjectives. The study also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We traced four learners over a period of 9 months in their use of haluta 'want' and tykätä 'like'. The verbs were relatively frequent in our data and can be considered good material for comparison because they are similar both semantically and structurally: they can both be seen to express an evaluation towards something (see Lesonen, Suni, Steinkrauss, & Verspoor, 2017), and they allow the same kinds of complements (see §3.3 below). The term 'lexically specific' is used to refer to a construction in which the main verb, here haluta or tykätä, repeatedly takes the same form (e.g., the first person singular) and the lexical material in the complement shows little variation.…”
Section: The Usage-based Learning Trajectorymentioning
confidence: 90%
“…We traced four learners over a period of 9 months in their use of haluta 'want' and tykätä 'like'. The verbs were relatively frequent in our data and can be considered good material for comparison because they are similar both semantically and structurally: they can both be seen to express an evaluation towards something (see Lesonen, Suni, Steinkrauss, & Verspoor, 2017), and they allow the same kinds of complements (see §3.3 below). The term 'lexically specific' is used to refer to a construction in which the main verb, here haluta or tykätä, repeatedly takes the same form (e.g., the first person singular) and the lexical material in the complement shows little variation.…”
Section: The Usage-based Learning Trajectorymentioning
confidence: 90%
“…In recent years, many researchers have adopted a CDST/DUB approach to study the role of variability in L2 development. It has been shown that a learner's performance fluctuates when measured with both specific and holistic measures (Spoelman & Verspoor, 2010;Tilma, 2014;Verspoor et al, 2008;Verspoor et al, 2017). Research has also demonstrated that learners whose language exhibits substantial variability may be more successful than their less-variable peers (Chan et al, 2015;Huang et al, 2021;Lowie & Verspoor, 2019).…”
Section: Tracing L2 Learners' Language Constructions: a Dub Approachmentioning
confidence: 99%
“…) In L2 learning, however, findings have been mixed. In some cases, learners use item-based constructions initially (Eskildsen, 2009;Eskildsen & Cadierno, 2007;Mellow, 2006); in other cases, there is more variability in the early constructions (Lesonen et al, 2017;Lesonen et al, 2020;Roehr-Brackin, 2014). The differences between L1 and L2 may be explained by the fact that L2 learners are already conversant with slot-finding and need less time to discover them.…”
Section: Tracing L2 Learners' Language Constructions: a Dub Approachmentioning
confidence: 99%
“…One finding that is consistently emerging from the growing body of usage-based research is that the exemplar-based trajectory is not necessarily a path from "one to many" but can also be from "a few to more" in a process where constructions that are partially specific and partially schematic (for example, "Are you + ADJECTIVE?" in L2 English question formation) play an essential role across phases in development (Eskildsen, 2015, Eskildsen 2017, Eskildsen 2020aLesonen et al, 2018, Lesonen et al, 2020a, Lesonen et al, 2020bHorbowicz and Nordanger, 2022). However, recent research is showing that a usage-based trajectory may also be a matter of routinisation (Eskildsen, 2020a;Pekarek Doehler and Balaman, 2021).…”
Section: Longitudinal Conversation Analysis-based and Usage-based Studies In L2 Researchmentioning
confidence: 99%